DNA methylation and viral gene expression in adenovirus-transformed and -infected cells. - Vardimon, L (1980)
The level of DNA methylation in adenovirus type 2 (Ad2) and type 12 (Ad12) DNA was determined by comparing the cleavage patterns generated by the isoschizomeric restriction enzymes HpaII and MspI. As previously reported virion DNA of Ad2 and Ad12 is not methylated. Parental or newly synthesized Ad2 DNA in productively infected human KB or HEK cells is not methylated either, nor is the integrated form of Ad2 DNA in productively infected cells. Hamster cells and Muntiacus muntjak cells are abortively infected by Ad12. We have not detected methylation of Ad12 DNA in hamster or Muntiacus muntjak cells. An inverse correlation between the level of methylation and the extent of expression of viral DNA in Ad12-transformed hamster cells has been described earlier. A similar relation has been found for the EcoRI fragment B of Ad2 DNA which is not methylated but is expressed as the Ad2 DNA-binding (72K) protein in the Ad2-transformed hamster line HE1. Conversely, the same segment is completely methylated in lines HE2 and HE3, and there is apparently no evidence for the expression of the 72K protein in these cell lines.